(untitled) (CIPEEX, 2024)
THE EXPONENTIAL EVOLUTION OF COMPUTER HARDWARE TECHNOLOGY HAS RESULTED IN A SCENARIO WHERE USERS HAVE A WIDE VARIETY OF OPTIONS FOR BUILDING THEIR OWN MACHINES. HOWEVER, THIS ABUNDANCE OF CHOICES CAN BE OVERWHELMING AND LEAD TO INCOMPATIBILITIES, A FREQUENT PROBLEM FACED BY ENTHUSIASTS AND BEGINNERS ALIKE. IN THIS CONTEXT, THERE IS A NEED FOR AN INNOVATIVE SYSTEM THAT SIMPLIFIES THE SELECTION OF COMPATIBLE COMPONENTS AND PROVIDES DETAILED INFORMATION ABOUT THEM. CHOOSING A CPU, MOTHERBOARD, MEMORY, GRAPHICS CARD AND OTHER COMPONENTS THAT WORK HARMONIOUSLY CAN BE COMPLEX AND TIME-CONSUMING. FURTHERMORE, ENSURING DRIVER COMPATIBILITY FOR THESE COMPONENTS IS AN ADDITIONAL AND OFTEN FORGOTTEN TASK, WHICH CAN LEAD TO PERFORMANCE ISSUES AND SYSTEM INSTABILITY. TO ADDRESS THIS ISSUE, IT WAS PROPOSED TO CREATE AN INNOVATIVE WEBSITE THAT OFFERS A COMPREHENSIVE SOLUTION FOR EVALUATING THE COMPATIBILITY OF COMPUTER COMPONENTS AND CHECKING THE HARMONY OF DRIVERS.